2015
DOI: 10.1530/eje-15-0646
|View full text |Cite
|
Sign up to set email alerts
|

Referral bias in female functional hyperandrogenism and polycystic ovary syndrome

Abstract: Objective: Women with polycystic ovary syndrome (PCOS) seeking health care in the United States may be more obese and hyperandrogenic than those present in the general population. We aimed to assess the impact of referral bias on European women with functional androgen excess disorders. Design: Cross-sectional study. Methods: We studied two groups of patients: i) 368 consecutive patients referred to our clinic for the study of functional hyperandrogenism (FH) (referral patients); ii) 57 consecutive premenopaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 28 publications
0
21
1
1
Order By: Relevance
“…A more recent study from Spain confirmed these findings in part. Luque-Ramírez et al (100) reported on patients with female functional hyperandrogenism and PCOS. They observed that patients with functional hyperandrogenism who sought medical care were more hirsute, had more pronounced clinical and biochemical HA, were more frequently obese, and had a higher prevalence of PCOS, as compared with patients identified in the general population.…”
Section: Referral Bias In Defining the Pcos Phenotypementioning
confidence: 99%
“…A more recent study from Spain confirmed these findings in part. Luque-Ramírez et al (100) reported on patients with female functional hyperandrogenism and PCOS. They observed that patients with functional hyperandrogenism who sought medical care were more hirsute, had more pronounced clinical and biochemical HA, were more frequently obese, and had a higher prevalence of PCOS, as compared with patients identified in the general population.…”
Section: Referral Bias In Defining the Pcos Phenotypementioning
confidence: 99%
“…Another potential of our study is the applicability of these results to women with PCOS in the general population. Previously, Luque-Ramirez et al suggested that patients with PCOS studied in the clinical setting may significantly differ from those in the general population in terms of androgen excess, obese phenotype and so forth (41).…”
Section: Strengths and Weaknesses Of Our Studymentioning
confidence: 99%
“…The mean intraassay and interassay CVs were <10% for all these assays. In‐house upper limit of normality for androstenedione and DHEAS has been reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…In-house upper limit of normality for androstenedione and DHEAS has been reported elsewhere. 16 All of the assays but the CDC-certified T method were run at the time of subjects' recruitments as described above. Both the external and local laboratories were blinded to women's features and patient or control status.…”
Section: Assaysmentioning
confidence: 99%